Studies of light liner compression dynamics in plasma focus - Karakin, M.A.; Khautiev, E.Yu.; Krauz, V.I.; Mokeev, A.N.; Myalton, V.V.; Smirnov, V.P. (Вопросы атомной науки и техники, 2003)
The study is devoted to the investigation of plasma focus systems as a driver for magnetic compression of liners. The experiments on the comparative analyse of the foam and multiwired liners compression were done on the Filippov-type plasma focus facility PF-3. The compression of the light (linear mass 0.3-0.6 mg/cm) liners with velocity (2-3).10⁶ cm/s was obtained. It is shown that under conditions of considerable radiation fluxes at the usage of strongly-radiating working gases a preliminary heating of the target can be attained. This results in acceleration of the transition of initially – condensed substance into plasma state, that assists in overcoming “cool start” problem.